Direct ink writing of graphite-Si electrode for Li-ion battery - Ng, Xian Qian (Nanyang Technological University, 2022)
Portable and renewable energy storage has found heavy uses in many industries and products. The lithium-ion battery is a breakthrough allowing great power, energy density and a long cycle life. As continued advancements are being made, it was realised that we may be reaching a limit to what we can achieve with the sandwich structure, where the need to increase energy density causes thicker structures but at the same raising ion diffusion length. This dilemma could be solved by manipulating the conventional structure to something more unique. With the use of 3D printing technology, Direct Ink Writing (DIW) it becomes possible to print electrodes with unique surface morphology that allows increased active loading material without increasing the ion diffusion length. In order to prove this point, DIW was used to fabricate electrodes with criss-cross shape. Before printing electrodes for comparison, rheological testing was done to ensure quality printing with the DIW system, line spacing was also tested before being compared with conventionally doctor bladed electrodes. The printed electrodes showed results rivalling the coated electrodes, with similar or higher active loading material, the printed electrodes showed discernibly better results in the cyclic voltammetry and impedance test, while the life cycle is shown to be unable to reach that of coated electrodes, it was very close. The results proved that DIW electrodes are a viable method for battery fabrication.